Breaking Hollywood’s Stereotypes: Arab Americans Respond - Mohammed Amin Medjabra; Abdelhak Elaggoune (The Journal of Studies in Language, Culture and Society)
This article sheds light on the stereotypical representations of Arab Americans in Hollywood. It focuses on the response of Arab Americans to the increasing outrageous stereotypes of the industry in post 9/11 America. Hollywood has always dehumanized and demonized the Arab and Muslim characters in its movies and presented them as terrorists. The research explores how Arab American independent moviemakers and producers used counter-narratives and self-representation to challenge the long-established Hollywood’s stereotypes and provide a reasonable and authentic portrayal of Arab Americans. The rise of independent cinema offered a room for Arab Americans to showcase the cultural differences of their ethnic communities. To reach the objectives of this research, both descriptive and qualitative methods are employed. The paper concludes that the efforts made by Arab Americans to counter Hollywood’s stereotypes managed to have their voices heard and prompted them to continue their struggle against media racial stereotyping.